Մակարոնիկ բանաստեղծական ձևը հայ վաղ նոր շրջանի բանաստեղծության մեջ` ԺԷ դարի հեղինակ Ավետիք Դաշտեցու ստեղծագործության օրինակով - Կիրակոսյան, Հասմիկ
The presence and diffusion of the macaronic poetic form within Eastern literature during the early modern period are indicative of the dynamic exchanges occurring in the region, characterized by close cross-cultural relations and interactions. This poetic form found expression in medieval Armenian poetry and holds significance in the classification of Armenian-Iranian literary relations, as evidenced by the works of Avetik Dashtetsi. Notably, bilingual and trilingual poems by figures such as Nahapet Kuchak, Grigoris Aghtamartsi, and Davit Saladzortsi exemplify this phenomenon. These authors adeptly incorporated poetic forms rooted in Iranian literature, such as mulammaʿ and musallasatʿ, demonstrating both their literary versatility and their engagement with contemporary literary trends. This integration underscores the Armenian poets' ability to navigate and contribute to the broader literary and cultural landscape of their time.
Keywords: միջնադարյան բանաստեղծություն; Բանասիրություն